SERVICE QUALITY AND PRICE ON CUSTOMER SATISFACTION WITH ELECTRONIC WORD OF MOUTH AS MODERATING VARIABLES - Khalimatus Sadiyah; Elliv Hidayatul Lailiyah; Sri Yaumi; Sawabi Sawabi (Universitas Malahayati, 2022)
This study aims to examine the effect of service quality and price on Customer satisfaction with electronic word of mouth as a moderating variable. This research is a quantitative research with a descriptive approach. The sample in this study are Customers who make purchases at CV. Amelia Sukses Mandiri Lamongan, totaling 100 respondents. The data used in this study are primary data collected through a questionnaire survey. Data analysis used Moderated Regression Analysis (MRA). The results showed that service quality had an effect on customer satisfaction. Price has an effect on Customer satisfaction. Electronic word of mouth is able to moderate the effect of service quality on Customer satisfaction, as well as electronic word of mouth is able to moderate the effect of price on Customer satisfaction.